2011
DOI: 10.2466/07.15.16.21.pr0.109.6.879-895
|View full text |Cite
|
Sign up to set email alerts
|

Child's and Parents' Catastrophizing about Pain is Associated with Procedural Fear in Children: A Study in Children with Diabetes and Their Mothers

Abstract: The contribution of the child's and parents' catastrophizing about pain was explored in explaining procedural pain and fear in children. Procedural fear and pain were investigated in 44 children with Type I diabetes undergoing a finger prick. The relationships between parents' catastrophizing and parents' own fear and estimates of their child's pain were also investigated. The children and their mothers completed questionnaires prior to a routine consultation with the diabetes physician. Children completed a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 48 publications
1
39
2
Order By: Relevance
“…Although some investigators using static pain tasks have found links between catastrophizing and pain reactivity among children, 26,33,49 others did not find such relationships. 4,39 It may be that the association between CPM and catastrophizing is less robust among children than it is in adults.…”
Section: Discussionmentioning
confidence: 93%
“…Although some investigators using static pain tasks have found links between catastrophizing and pain reactivity among children, 26,33,49 others did not find such relationships. 4,39 It may be that the association between CPM and catastrophizing is less robust among children than it is in adults.…”
Section: Discussionmentioning
confidence: 93%
“…First are studies examining the impact of parental emotions and thoughts regarding the child’s experience on the child’s pain outcomes. For example, one study found associations between parental catastrophizing/fear about the child’s pain and child-reported fear of medical procedures 28. The child’s sex was controlled in analyses, rather than examined separately, suggesting that the findings held for both boys and girls.…”
Section: Discussionmentioning
confidence: 99%
“…For details of the second part, see Vervoort et al (2011). In the hospital the research assistant obtained written parent consent and child assent.…”
Section: Methodsmentioning
confidence: 99%
“…Findings pertaining to other study aims have been reported elsewhere (see Vervoort et al, 2011). To be eligible for participation, the child (a) had to be diagnosed with T1D, (b) aged 8-15 years, (c) was not suffering another physical or pervasive developmental disorder, and (d) parent and child had to be Dutch-speaking.…”
Section: Participantsmentioning
confidence: 99%